Evaluation of cerebrospinal fluid ubiquitin C-terminal hydrolase-L1, glial fibrillary acidic protein, and neurofilament light protein as novel markers for the diagnosis of neurosyphilis among HIV-negative patients. (February 2023) - Chen, Rui; Lin, Li-Rong; Xiao, Yao; Ke, Wu-Jian; Yang, Tian-Ci
HIGHLIGHTS: Sensitive, easy-to-perform diagnostic markers for early neurosyphilis (NS) are vital. Patients with NS gave higher cerebrospinal fluid ubiquitin C-terminal hydrolase L1 (CSF UCH-L1), glial fibrillary acidic protein (GFAP), and neurofilament light protein (NF-L) as indicators of neuronal damage. CSF UCH-L1, GFAP, and NF-L had high screening performance for patients with NS who are HIV-negative. CSF UCH-L1, GFAP, and NF-L were markers for NS, independent of rapid plasma reagin, white blood cells, and protein. ABSTRACT: Objectives: To evaluate the possibility of using cerebrospinal fluid (CSF) ubiquitin C-terminal hydrolase L1 (UCH-L1), glial fibrillary acidic protein (GFAP), and neurofilament light protein (NF-L) for the diagnosis of neurosyphilis (NS). Methods: A cross-sectional study of 576 subjects was conducted at Zhongshan Hospital from January 2021 to August 2022 to evaluate the diagnostic accuracy of CSF UCH-L1, GFAP, and NF-L for NS and analyze their correlations with CSF rapid plasma reagin (RPR), white blood cells (WBCs), and protein. Results: Patients with NS had higher CSF UCH-L1, GFAP, and NF-L levels than patients with syphilis/non-NS and nonsyphilis. Using a cut-off point of 652.25 pg/ml, 548.89 pg/ml, and 48.38 pg/ml, CSF UCH-L1, GFAP, and NF-L had a sensitivity of 85.11%, 76.60%, and 82.98%, with a specificity of 92.22%, 85.56%, and 91.11%, respectively, for NS diagnosis. Moreover, parallel and serial testing algorithms improved their sensitivity and specificity to 93.62% and 98.89%, respectively. Interestingly, levels between patients with NS who are CSF RPR-positive and -negative did not differ and showed a weak or moderate correlation with WBC and CSF protein in patients with syphilis. Conclusion: CSF UCH-L1, GFAP, and NF-L can be used as novel markers for the diagnosis of NS, independent of CSF RPR, WBC, and proteins.